Microsoft Project 2016 Training (Basic & Intermediate) - Sorooshian, Shahryar (FIM-UMP, 2016)
This three-day training (6th Apr - 8th Apr 2016) was conducted by experienced instructors for lecturers who were interested in expanding their knowledge base and technical skills about Microsoft Project.